Answer:
√(p²-4q)
Step-by-step explanation:
Using the Quadratic Formula, we can say that
x = ( -p ± √(p²-4(1)(q))) / 2(1) with the 1 representing the coefficient of x². Simplifying, we get
x = ( -p ± √(p²-4q)) / 2
The roots of the function are therefore at
x = ( -p + √(p²-4q)) / 2 and x = ( -p - √(p²-4q)) / 2. The difference of the roots is thus
( -p + √(p²-4q)) / 2 - ( ( -p - √(p²-4q)) / 2)
= 0 + 2 √(p²-4q)/2
= √(p²-4q)
Answer:
x = 10
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
BecASUE D IS THE NEXT IN THE PATTERN.
AngleA= angle D
5x+2=87
5x=85
X=17
180-87-42=51
Angle C= angle F
3y=51
Y=17
Answer: I’m not sure but I think the answer is $255
Step-by-step explanation: